2020
DOI: 10.1101/2020.06.11.146126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phytohormone production by the arbuscular mycorrhizal fungusRhizophagus irregularis

Abstract: 20 * Correspondence to: puech@lrsv.ups-tlse.fr, +33 (0)5 34 32 38 31 (VPP) and frei-dit-21 frey@lrsv.ups-tlse.fr (NFdF), +33 (0)5 34 32 38 60 22 23 Text word count: 5465 24 Number of figure: 3 25 -Fig. 1 Detection by LC-MS of iPR and IAA exuded by R. irregularis spores (colour print) 26 -Fig. 2 GA 4 detection in multiple reactions monitoring (MRM) mode (colour print) HIGLIGHT 31 In this work, we provide for the first time direct experimental evidence, by mass 32 spectrometry and gas chromatography analyses, th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Remarkably, the content of ABA in AM fungi is more than one order of magnitude higher than that in plant roots (Esch et al, 1994). Pons et al (2020) provided direct evidence that AM fungi can synthesize cytokinins, auxin, gibberellins, and ethylene but not ABA, which indicates that ABA in AM fungi is derived from plants. Therefore, functional genes responsible for ABA biosynthesis in AM fungi or transporters responsible for transporting ABA from the roots to AM fungi remain unexplored.…”
Section: Abscisic Acid Regulationmentioning
confidence: 98%
“…Remarkably, the content of ABA in AM fungi is more than one order of magnitude higher than that in plant roots (Esch et al, 1994). Pons et al (2020) provided direct evidence that AM fungi can synthesize cytokinins, auxin, gibberellins, and ethylene but not ABA, which indicates that ABA in AM fungi is derived from plants. Therefore, functional genes responsible for ABA biosynthesis in AM fungi or transporters responsible for transporting ABA from the roots to AM fungi remain unexplored.…”
Section: Abscisic Acid Regulationmentioning
confidence: 98%
“…The SA is dispersed over several centimeters and is transformed into its volatile derivatives, which then alter the structure of microbial communities (Dehimeche et al, 2021;Kong et al, 2021). Notably, Pons et al (2020) found that phytohormones including cytokinin (isopentenyl adenosine), an auxin (indole-acetic acid), gibberellin (gibberellin A4), and ethylene are also produced by the AM fungus Rhizophagus irregularis. Similarly, the EM fungus Tricholoma vaccinum emits ethylene and excretes ABA, SA, jasmonates, and indole-3-acetid acid (Abdulsalam et al, 2021).…”
Section: Mycorrhizae Shape the Rhizosphere Microbiomementioning
confidence: 99%